TINJAUAN HUKUM HUBUNGAN KEMITRAAN ANTARA EKSEKUTIF DAN LEGISLATIF DALAM PENYELENGGARAAN PEMERINTAHAN DAERAH - Nila Trisna (Jurnal Public Policy, 2017)
The Regional People's Legislative Assembly (DPRD) is a form of representative institution of the people of provinces, districts, or cities in Indonesia which is located as an element of local government administration together with the Regional Government. The existence of the Regional People's Legislative Assembly is regulated, among others, in Law Number 27 Year 2009 concerning the People's Consultative Assembly, the People's Legislative Assembly, the Regional Representative Council, and the Regional People's Legislative Assembly. Article 342 of Law Number 27 Year 2009 stipulates that "Regency / Municipal DPRD shall be a regional representative body domiciled as the element of the regional administration of a regency / municipality. In formal juridical, DPRD is the working partner of Regional Head either Governor, Regent, or Mayor. Since the enactment of Law Number 32 Year 2004 regarding Regional Government, the Regional Head shall no longer be responsible to the Regional People's Legislative Assembly, since it shall be elected directly by the people through the election of the Regional Head and Deputy Regional Head. Article 27 Paragraph (2) of Law Number 32 Year 2004 stipulates, among other things, that "the Regional Head has an obligation also to provide reports on the implementation of regional government to the Government, and to give accountability report to the DPRD". Nevertheless, the role of DPRD is enormous in determining regional policy.This study uses the normative juridical method, which is the approach done by examining the legislation relevant to the problem under study or looking from the normative legal aspects. Technique of data collection is done by Research of Library (Library Research), that is by studying book and literature relevant with writing. Keywords: Executive, Legislative.Relationship Partnership